EXPLORING ENGLISH TEACHERS' EXPERIENCES UNDER THE MERDEKA CURRICULUM - Dwi Harum Anasthasya; Raden Muhammad Ali; Habizar (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The purpose of this study to explore English teachers’ experiences in implementing the Merdeka Curriculum at one of the vocational schools in Merangin. Using a descriptive qualitative method with a phenomenological approach, two participants from a vocational school were involved in this study. The data were collected through interviews and subsequently analyzed. This study explored English teachers’ perspectives on the challenges they faced in teaching English in the classroom and the strategies they employed to address those challenges. The findings revealed that the challenges were related to student-related factors and school-related factors. The challenges included a lack of training, pedagogical difficulties, motivational issues, time management constraints, student heterogeneity in the classroom, inadequate school facilities and infrastructure, and limited parental support. To overcome these challenges, teachers applied strategies such as improving their digital skills, utilizing free online learning resources, collaborating with fellow teachers, and designing more flexible lesson plans.